Impact of 35% Hydrogen Peroxide on Color and Translucency Changes in Enamel and Dentin - Menezes,Rebeca Pereira de (2018)
Abstract This study evaluated the effects of tooth bleaching with high-concentration of hydrogen peroxide on alterations of translucency parameter (TP) and color of dentin and enamel. The crown of five human molars was sectioned into four slices parallel to buccal surface. The dentin of external slices containing buccal/ lingual enamel was fully removed with diamond bur; while these slices were used to assess alterations on enamel. Alterations on dentin were assessed into the center of internal slices. The color of specimens was measured over white and black backgrounds using a spectrophotometer (CieL*a*b) at baseline, allowing to calculate the TP by difference between the color measured over each background. Specimens were submitted to three 15-min applications of 35% hydrogen peroxide followed by their storage in water for one-week. Afterwards, the color measurements were repeated at both backgrounds. Color (∆L, ∆a, ∆b and ∆E) and translucency (∆TP) changes were calculated and data individually analyzed by T-test (α = 0.05). Influence of hard tissue and assessment time on each color parameter was also analyzed by 2-way repeated measure ANOVA (α = 0.05). Tooth bleaching resulted in increased lightness for the enamel, whereas no alteration on this parameter occurred for dentin. No difference between the tooth hard tissues was observed regards the other color parameters and ∆E. A slightly reduction on TP was observed only for the enamel. In conclusion, 35% hydrogen peroxide caused similar color and translucency changes on dentin and enamel.